High Serum IgG4 Concentrations in Patients with Hashimoto's Thyroiditis. (16th February 2015) - Popławska-Kita, Anna; Kościuszko-Zdrodowska, Maria; Siewko, Katarzyna; Telejko, Beata; Hryniewicka, Justyna; Milewski, Robert; Abdelrazek, Saeid Soleman; Szelachowska, Małgorzata; Górska, Maria
Abstract : Purpose . Since recent reports suggest that Hashimoto thyroiditis (HT) may be associated with IgG4-related disease, we aimed to find out whether the measurement of serum IgG4 allows for the identification of distinct types of HT, with different clinical, sonographic, and serologic characteristics. Methods . The group studied consisted of 53 patients with HT and 28 healthy individuals who underwent thyroid ultrasonography and body composition analysis. Serum concentrations of IgG4, TSH, anti-peroxidase antibodies (TPOAb), anti-TSH receptor antibodies, TNF- α, TGF- β 1, Fas Ligand, TRAIL, and chemokines (CXCL9, CXCL11, and CXCL10) were measured by ELISA or radioimmunoassay. Results . The group with IgG4 level >135 IU/ml accounted for 32.5% of the patients. The signs of fibrosis were present in 27.0% of the high-IgG4 patients and in 9.1% of the normal-IgG4 group. The patients with elevated IgG4 required higher doses of L-thyroxine and had significantly lower level of TPOAb (P = 0.02 ) than the non-IgG4-HT individuals and higher TNF- α level in comparison with the controls (P = 0.01 ). Conclusions . Our results suggest that the measurement of serum IgG4 allows for an identification of patients with more rapid progression of HT, requiring higher doses of L-thyroxine. Low TPOAb level and the absence of coexisting autoimmune diseases may suggest distinct pathomechanism of this type of thyroiditis.